130 Presynchronization with Prostaglandin F2αand prolonged exposure to exogenous progesterone impacts estrus expression and alters fertility in beef heifers. (28th November 2020) - Oosthuizen, Nicola; Fontes, Pedro; Lamb, Cliff
Abstract: To determine the effects of 2 presynchronization strategies in conjunction with delayed fixed-time artificial insemination (TAI) on pregnancy rates to TAI (PR/AI), 1, 700 Angus beef heifers at 3 locations were enrolled in a completely randomized design with a 2×2 factorial arrangement of treatments. Within location, all heifers were randomly assigned to 1 of 4 treatments: 1) PG54 (n = 434), heifers received a 25-mg injection of prostaglandin F2α (PGF) 7 d prior (d -14) to the initiation of the 7-d CO-Synch + CIDR protocol wherein they received a 100-µg injection of gonadotropin-releasing hormone (GnRH) and a CIDR insert on d -7, a 25-mg injection of PGF at CIDR removal on d 0, and a second injection of GnRH concurrently with TAI 54±2 h later; 2) PG72 (n = 426), heifers were exposed to the same treatment as PG54; however, TAI was performed 72 ± 2 h after CIDR removal; 3) PG-CIDR54 (n = 422), same as PG54 but heifers received a CIDR insert on d -14 in addition to PGF; 4) PG-CIDR72 (n = 418), same as PG-CIDR54; however, TAI was performed 72±2 h after CIDR removal. Estrus detection patches were applied to all heifers on d 0 and were evaluated for activation at TAI. Pregnancy was diagnosed between 30 and 47 d after TAI. The percentage of heifers exhibiting estrus between d 0 and TAI was greater (P < 0.001) in the PG72, PG-CIDR54, and PG-CIDR72 treatments compared to the PG54 treatment (78.11, 86.59, and 91.09 vs. 31.05%, respectively). Furthermore, estrus response was greater (P < 0.001) in PG-CIDR72 heifers when compared to PG72. Pregnancy rates to TAI differed among treatments and were greater (P < 0.05) in the PG72 and PG-CIDR54 treatments when compared to PG-CIDR72 (48.8 and 50.4 vs. 38.4%, respectively), and were greater (P = 0.034) in PG-CIDR54 vs. PG54 (43.1%). Moreover, a tendency (P = 0.097) was determined on PR/AI between PG54 and PG72. In conclusion, presynchronization strategies and prolonged exposure to exogenous progesterone have the potential to alter estrus expression and improve fertility in replacement beef heifers.